Square technique-A treatment for cellulite with large size particle hyaluronic acid - Luciana deMatos Lourenço; Lara Apendino Colla; Maria Gabriela Ortiz de Noronha; Thomaz Rezende Izzo; Rosa Sigrist (Wiley, 2024)
Abstract Gynoid lipodystrophy, also called cellulite, is defined as a metabolic disorder of the subcutaneous tissue that alters body contour. It is rare in men but affects 80%-90% of adult women.The authors describe a technique for the treatment of cellulite with non‐traumatic subcisionTM of septa by cannula associated with large‐gel‐particle hyaluronic acid (HA). It uses a special marking, a safe plan and a specific product. The product being used is Subskin Aeskins, in a subcutaneous plan as no major blood vessels were found.The authors report good aesthetic results with the proposed technique. The patients reported a high degree of satisfaction.The product chosen has high G prime and large particles, which accounts for resistance to deformation and a high lifting power. Moreover, HA is a biocompatible, absorbable product and considered a safe filler. This technique allows the treatment of an area with various surface irregularities.The Square Technique proved to be a minimally invasive technique, with fast results, no major risks and little downtime, bringing satisfaction to patients and improving their self‐confidence and quality of life.